Observation of Incretin Effects During Enteral Feed Transitions of Critically Ill Patients - Ummu Kulthum, Jamaludin; Docherty, Paul D.; Chase, J. Geoffrey; Le Compte, Aaron; Shaw, Geoffrey M.; Desaive, Thomas; Preiser, Jean-Charles (Elsevier, 2012)
Background & aims: Critically ill patients are regularly feed via constant enteral (EN) nutrition infusions. However, the incretin effect or its impact on endogenous insulin concentration remains unclear. This study determines whether there is an EN-driven incretin effect in critically ill patients requiring glycaemic control.